EKSPANSI ABSES BUKAL SINISTRA KEARAH COLLI DAN THORAKS DISERTAI PERFORASI GASTER - Yayun Siti Rochmah (Faculty of Dentistry, Universitas Islam Sultan Agung, 2018)
Background: Abscess is infection caused of anerob bacteria. Maxillofacialabcess aetiology was oral focus infection like dental gangren. Unproportionaltreatment could make complication that makes sistemic condition patient worst,gaster perforation. Objective : to present treatment bucal abscess case thatexpanding to colli, thoraks and complication based on mistherapy about NSAIDwith gaster perforation.Case and management: A 59 years old man with chief complain colli abscessand suspect gaster perforation with diffuse abdominal pain and distensiongaster since three days. Intraoral inspection was multipel dental gangren.Ultrasonography showed gaster perforation. Incicion drainase was done anderadication oral focus infection with repair gaster perforation under generalanaesthesia prosedure. Medication treatment with ceftriaxone injection 2x1 gram, and paracetamol infus 3x 500 mg. Bacteria kulture was negatif andhospitalization patient until 1 week.Discussion: Gold standart abscess therapy is incision drainase, but there wereclinician not aware abiut that and choosed konservative treatment with antibioticand analgesic, so that less maximal theraphy. Complication NSAID analgesicwas gaster iritation, so unproportional drug treatment can lead gaster ulcerationor perforation.Conclusion: It is important and consider drug choise for abscess treatment toavoid worst complication development